Distribution of gold derived from hydrothermal fluids on the modern seafloor and its impact on the gold budget of seawater - Wei Huang; Jin Liang; Jingfang Lu; Fanghui Hou; Panfeng Li; Ruyong Cui (Frontiers in Marine Science, 2023)
The modern seafloor hydrothermal system plays a significant role in the cycling of energy and mass between the internal and external layers of the oceanic crust and upper mantle. It continues to supply hydrothermal fluids containing three to five orders of magnitude more gold into the ocean than the amount typically present in deep seawater. It has a considerable impact on the distribution and budget of gold with respect to the large geological inventory of the ocean along with other input sources such as river water. The large amount of various types of data compiled for this study reveals that only about 0.3% of the annual hydrothermal flux of gold (2618.3 kg/a) injected into the overlying seawater column as a dissolved phase is eventually trapped in sulfide deposits near vent sites on the seafloor, while about 0.8% is trapped in metalliferous sediments that fall out from the distal nonbuoyant plume. The remaining ~98.9% of gold is delivered into the depths of the global open ocean. The global budget of gold in seawater (about 1.4 × 10 7 kg), the annual flux of hydrothermal fluids at the seafloor (about 2.6 × 10 3 kg/a), the amount delivered by river water (about 7.2 × 10 4 kg/a), and significant estuarine removal (15%) allows us to estimate the residence time of gold in the modern ocean to be about 220 years. This value is 70% shorter than that (~1000 years) reported previously. In the future, the use of appropriate artificial means to achieve more efficient precipitation of gold from the hydrothermal system at the seafloor could increase the level of enrichment of gold to obtain gold-rich hydrothermal deposits, yielding greater economic benefits.